PENGARUH LEVEL PROTEIN PAKAN YANG BERBEDA PADA MASA STARTER TERHADAP PENAMPILAN AYAM KAMPUNG SUPER - Harimurti Februari Trisiwi (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
The experiment was conducted to study the effects of different starter dietary protein levels (0-8 weeks) on performance and carcass production of super native chicken. P1 used starter broiler. P2 and P3 diets were formulated in which the dried bakery product was incorporated at levels 20 and 40% with essential amino acid (EEA) correction to determine whether EAA correction of a lower protein diet would enhance performance. Fourty eight unsexed day old chicken were randomly divided into 3 groups of treatment in 4 replications and consisted of 4 bird each. The chickens were kept up to 8 weeks receiving 3 ration treatments i.e. crude protein levels of 21,13% (P1),18,77% corrected with EEA (P2), and 16,42% corrected with EEA (P3). The collected data were analysed by a one way classification of variance analysis, followed by testing the significant means by Duncan’s Multiple Range Test. The result of the experiment showed that lowering the level of protein in the diet had very significant (P<0.01) effects on feed intake, body weight gain, feed conversion, final body weight, protein intake, protein efficiency ratio (PER), energy intake, energy efficiency ratio (EER), male liveweight, fat content of breast meat, and had significant effect (P<0.05) on male carcass weight. Keywords : Low Protein Diet, Essential Amino Acid, Performance, Carcass Production